Rapid automated selection of mammalian cell line secreting high level of humanized monoclonal antibody using Clone Pix FL system and the correlation between exterior median intensity and antibody productivity - Cheah, S.H.; Dharshanan, S.; Chong, H.; Zamrod, Z.; Kamal, N. (Elsevier, 2011)
The selection of high-producing mammalian cell lines is a crucial step in process development for the production of biopharmaceuticals. Previously, cloning by limiting dilution method was used to isolate monoclonal NS0 cells secreting high levels of humanized-C2 monoclonal antibodies. However limiting dilution method is time consuming, has low probability of monoclonality and is significantly limited by the number of clones that can be feasibly screened. In order to minimize the duration and to increase the probability of obtaining high-producing clones with high monoclonality, an automated colony picker, Clone Pix FL system was used to replace limiting dilution method. We were able to screen 1 x 105 clones secreting humanized monoclonal antibodies and high producer clones were selected in just 7 days. Briefly, semi-solid media was used to immobilize single cells separately and allow them to proliferate into discrete clones. The high viscosity nature of the semi-solid media retains the secreted products in the vicinity of the associated clones. Using Clone Pix FL system, all clones were screened and the producer clones with different exterior fluorescent intensities were automatically isolated. We were able to isolate rare high-producers (> 3000 FU) with frequency of as low as 0.003% of the population. A quantitative ELISA was also performed to evaluate the correlation between the fluorescence intensity of clones with its corresponding antibody productivity. Clones with fluorescence intensity of < 1000 FU showed relatively low antibody productivity compared with those greater than 1000 FU; however above this there was no correlation of production with the increase in fluorescence intensity. Hence, although the high-throughput, rapid and automated nature of Clone Pix FL system allows the screening of large number of cells in a short period of time with also an increased in the probability of obtaining rare and precious high-producing clones, downstream analysis are still vital to determine the ‘actual’ and stable high producer clones.